Effect of environmental enrichment on anxiety: experimental study in an animal model: ENVIRONMENTAL ENRICHMENT INDUCES HYPERACTIVITY WITH DECREASED LEVELS OF ANXIETY - Suarez Rodríguez, Marian Andrea; Pulido Barrera, Silvana Paola; Durán Sira, Santiago José; Caicedo Pinto, Peter; Bonfante Cabarcas, Rafael Armando (Innovaciencia, 2021)
Anxiety is a global health problem; therefore, it is necessary to study new therapeutics alternatives, including environmental enrichment (EE). In the present paper the effect of EE on anxiety were studied. EE was evaluated in 20 C57BL/6 mice divided into 2 groups: Control Group (CG, n=10) and Experimental Group (EG, n=10). EG received EE with various sensory stimuli (olfatoy, gustatory, visual and tactile) and dark niches. CG was housed individually in a restricted environment. Mice were evaluated in the Elevated Plus Maze (EPM), Light/Dark Box (LDB) and Preference for Sucrose (PS). EE caused hypermotility in EPM with preference for shifts between closed arms (p<0.05), increased the unit residence time in both compartments of LDB (p<005) and significantly increased the PS (p<0.05). In conclusion; the EE based on including dark niches induces hyperactivity with decreased levels of anxiety, allowing the expression of instinctive behaviors to dark places.